Identification of Plasmodium falciparum var1CSA and var2CSA domains that bind IgM natural antibodies - Semblat, Jean-Philippe (2006)
Malaria in pregnancy is responsible for maternal anaemia, low-birth-weight babies and infant deaths. Plasmodium falciparum infected erythrocytes are thought to cause placental pathology by adhering to host receptors such as chondroitin sulphate A (CSA). CSA binding infected erythrocytes also bind IgM natural antibodies from normal human serum, a process that may facilitate placental adhesion or promote immune evasion. The parasite ligands that mediate placental adhesion are thought to be members of the variant erythrocyte surface antigen family P. falciparum erythrocyte membrane protein 1 (PfEMP1), encoded by the var genes. Two var gene sub-families, var1CSA and var2CSA, have been identified as parasite CSA binding ligands and are leading candidates for a vaccine to prevent pregnancy-associated malaria. We investigated whether these two var gene subfamilies implicated in CSA binding are also the molecules responsible for IgM natural antibody binding. By heterologous expression of domains in COS-7 cells, we found that both var1CSA and var2CSA PfEMP1 variants bound IgM, and in both cases the binding region was a DBL epsilon domain occurring proximal to the membrane. None of the domains from a control non-IgM-binding parasite (R29) bound IgM when expressed in COS-7 cells. These results show that PfEMP1 is a parasite ligand for non-immune IgM and are the first demonstration of a specific adhesive function for PfEMP1 epsilon type domains.